PERLINDUNGAN HUKUM TERHADAP PEREMPUAN YANG MELAKUKAN ABORSI AKIBAT HAMIL DI LUAR NIKAH - Purnama, Ni Kadek Dian Candra; Saimima, Ika Dewi Sartika; Noviriska (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Cases of women who become pregnant out of wedlock and their children certainly have various impacts resulting in abortion. The Criminal Code prohibits abortion, but Law no. 36 of 2009 concerning Health allows abortion but by providing the conditions contained in Article 76 of the Health Law. If the abortion does not comply with the requirements in Article 76 of the Health Law, then the child rape victim who undergoes an abortion may be subject to a crime under Article 194 of the Health Law. This research focuses on legal protection for children who are pregnant out of wedlock and undergo abortions. This research discusses Decision Number: Number 5/Pid.SusAnak/2018/PN.Mbn. In this case, it was stated that the child defendant had an abortion under the influence of coercion from her biological mother. Victims have the right to receive protection both materially and psychologically in the form of providing victims' rights during the case resolution process in accordance with the provisions contained in Article 7a of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims ( LPSK Law). Based on the provisions contained in the LPSK Law, victims of criminal acts are entitled to receive restitution in the form of: a. compensation for loss of wealth or income; b. compensation for losses incurred as a result of suffering directly related to criminal acts; and/or c. reimbursement for medical and/or psychological care. However, in this decision the victim has not received his rights